Power electronics for renewable energy systems, transportation, and industrial applications (Wiley, 2014)
Power Electronics for Renewable Energy, Transportation, and Industrial Applications combines state-of-the-art global expertise to present the latest research on power electronics and its application in transportation, renewable energy, and different industrial applications. This timely book aims to facilitate the implementation of cutting-edge techniques to design problems offering innovative solutions to the growing power demands in small- and large-size industries. Application areas in the book range from smart homes and electric and plug-in hybrid electrical vehicles (PHEVs), to smart distribution and intelligence operation centers where significant energy efficiency improvements can be achieved through the appropriate use and design of power electronics and energy storage devices.